Amorphous Tin Oxide as a Low-Temperature-Processed Electron-Transport Layer for Organic and Hybrid Perovskite Solar Cells - Amassian, Aram; Alarousu, Erkki; Mohammed, Omar F.; Neophytou, Marios; Murali, Banavoth; Abulikemu, Mutalifu; Del Gobbo, Silvano; Tietze, Max L.; McCulloch, Iain; Yue, Wan; Barbé, Jérémy M.; Labban, Abdulrahman El (My University, 2017)
© 2017 American Chemical Society. Chemical bath deposition (CBD) of tin oxide (SnO 2 ) thin films as an electron-transport layer (ETL) in a planar-heterojunction n-i-p organohalide lead perovskite and organic bulk-heterojunction (BHJ) solar cells is reported. The amorphous SnO 2 (a-SnO 2 ) films are grown from a nontoxic aqueous bath of tin chloride at a very low temperature (55 °C) and do not require postannealing treatment to work very effectively as an ETL in a planar-heterojunction n-i-p organohalide lead perovskite or organic BHJ solar cells, in lieu of the commonly used ETL materials titanium oxide (TiO 2 ) and zinc oxide (ZnO), respectively. Ultraviolet photoelectron spectroscopy measurements on the glass/indium-tin oxide (ITO)/SnO 2 /methylammonium lead iodide (MAPbI 3 )/2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene device stack indicate that extraction of photogenerated electrons is facilitated by a perfect alignment of the conduction bands at the SnO 2 /MAPbI 3 interface, while the deep valence band of SnO 2 ensures strong hole-blocking properties. Despite exhibiting very low electron mobility, the excellent interfacial energetics combined with high transparency (E gap,optical > 4 eV) and uniform substrate coverage make the a-SnO 2 ETL prepared by CBD an excellent candidate for the potentially low-cost and large-scale fabrication of organohalide lead perovskite and organic photovoltaics.
Keywords: chemical bath deposition; organic solar cells; perovskite solar cells; tin oxide electron-transport layer; ultraviolet photoelectron spectroscopy